Loss of CLOCK under high glucose upregulates ROCK1-mediated endothelial to mesenchymal transition and aggravates plaque vulnerability. (August 2018) - Tang, Hanfei; Zhu, Mengjiao; Zhao, Gefei; Fu, Weiguo; Shi, Zhenyu; Ding, Yong; Tang, Xiao; Guo, Daqiao
Abstract: Background and aims: Carotid atherosclerotic plaque is one of the main sources of ischemic stroke, and endothelial-to-mesenchymal transition (EndMT) is a major feature of atherosclerosis. Rho-associated coiled-coil-containing protein kinase 1 (ROCK1) activation, stimulated by high glucose, plays an important role in EndMT, and circadian locomotor output cycles protein kaput ( Clock ) deficiency leads to hyperglycemia and enhanced atherosclerosis in Clock Δ19/Δ19 apolipoprotein E ( ApoE ) −/− mice. These findings point to a mechanism whereby CLOCK exerts a protective effect against EndMT and atherosclerotic plaque accumulation. Methods: Cultured human umbilical vein endothelial cells (HUVECs) were stimulated with 66 mM glucose for 120 h to induce EndMT. The expression of CLOCK and ROCK1 was assayed, as were their effects on EndMT. We also conducted molecular and morphometric examination of carotid artery plaques from patients with carotid artery stenosis to assess the clinical relevance of these findings. Results: Upon EndMT, HUVECs exhibited decreased CLOCK expression and increased ROCK1 expression. Notably, CLOCK silencing increased high glucose-induced EndMT, migration ability, and ROCK1 activation, while overexpressing CLOCK attenuated these characteristics. Moreover, inhibition of ROCK1 largely blocked EndMT induced by high-glucose or transforming growth factor (TGF)-β1 but failed to rescue the reduced CLOCK expression. The vulnerability of human carotid artery plaque was strongly correlated with loss of CLOCK expression, activation of TGF-β/ROCK1 signaling, and the extent of EndMT. Conclusions: The data indicate that loss of protective endothelial CLOCK expression aggravates TGF-β/ROCK1-modulated EndMT progression, which contributes to the vulnerability of human carotid plaque. Highlights: Atherosclerosis involves endothelial to mesenchymal transition (EndMT). CLOCK controls high glucose-induced EndMT in human endothelial cells. Inhibition of ROCK1, downstream of CLOCK, prevents EndMT. CLOCK and EndMT levels correlate with human carotid plaque vulnerability. CLOCK-ROCK1 signaling may be a valuable therapeutic target for atherosclerosis.